2018
DOI: 10.2147/cmar.s164911
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of lncRNA OGFRP1 inhibits hepatocellular carcinoma progression by AKT/mTOR and Wnt/β-catenin signaling pathways

Abstract: IntroductionIncreasing evidence demonstrates that long noncoding RNAs (lncRNAs) play important roles in the progression of hepatocellular carcinoma (HCC) by regulating gene expression. However, the identification of functional lncRNAs in HCC remains insufficient. Our study aimed to investigate the function of lncRNA OGFRP1, which has not been functionally researched before, in Hep3B and HepG2 cells.MethodslncRNA OGFRP1 in HCC cells was down-regulated by using RNAi technology. Quantitative real-time polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 44 publications
2
37
0
Order By: Relevance
“…Aberrant activation of this pathway occurs in many malignant tumours including endometrial cancer [17,37]. In addition, the downregulation of OGFRP1 has been revealed to inhibit hepatocellular carcinoma via the regulation of AKT/mTOR and Wnt/b-catenin signals [19]. Koga et al pointed out that the PI3K/AKT/GSK-3b signals is crucial to SIRT1 induction by stress reaction of endoplasmic reticulum and consequently regulates hepatocellular injury [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant activation of this pathway occurs in many malignant tumours including endometrial cancer [17,37]. In addition, the downregulation of OGFRP1 has been revealed to inhibit hepatocellular carcinoma via the regulation of AKT/mTOR and Wnt/b-catenin signals [19]. Koga et al pointed out that the PI3K/AKT/GSK-3b signals is crucial to SIRT1 induction by stress reaction of endoplasmic reticulum and consequently regulates hepatocellular injury [38].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that lncRNA DLEU1 enhances the progression of endometrial cancer through activation of PI3K/AKT/GSK-3b pathway [18]. Moreover, OGFRP1 downregulation was shown to inhibit hepatocellular carcinoma by regulating AKT/mTOR and Wnt/b-catenin signals [19]. We investigated whether activation of PI3K/AKT/GSK-3b pathway is a key mechanism that mediates the role of OGFRP1 in endometrial cancer.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Interestingly, studies have shown that activated AKT could result in phosphorylation and inactivation of GSK3β [13,14], which therefore promotes β-catenin accumulation and nuclear translocation in Wnt/β-catenin pathway [15]. These previous findings indicate the crosstalk between AKT/mTOR and Wnt/β-catenin signaling pathways, and the regulation of these two pathways has also been reported in several cancers [16,17]. Although both AKT/mTOR and Wnt/β-catenin pathways have been investigated in cervical cancer respectively [18,19], no studies have been reported on the regulation of these pathways by GHET1 in CC.…”
Section: Introductionmentioning
confidence: 76%
“…. For example, downregulation of lncRNA OGFRP1 can inhibit HCC progression through AKT/mTOR signaling (Chen, You, Zheng, & Zhu, 2018). PTTG3P promotes HCC progression via upregulating PTTG1 and PI3K/AKT (Huang et al, 2018).…”
mentioning
confidence: 99%